Supervisão acadêmica do Projeto Mais Médicos para o Brasil: uma análise de suas potencialidades e propostas pedagógicas - Alencar, Mariana Amorim (2018)
This research addressed the Academic Supervision of the More Doctors Project for Brazil (PMMB) of the Federal University of Ceará (UFC). We sought to analyze its development, to reflect on its practices, to discuss the possibility of new interventions, in order to build with the supervisors an action plan. The PMMB integrates one of the three structuring actions of the More Doctors Program (PMM), whose purpose is to train Doctors for the Unified Health System (SUS). This Project seeks to achieve professional improvement through teaching service integration, according to the logic of permanent education. The Academic Supervision has the mission of offering support to the participating physicians to strengthen the skills needed to work in primary health care. Despite the determinations in the current regulations, we believe that there isn´t no clear definition of the role that the supervisor should assume in this Project and the supervision methodology to be used. This has enabled different experiences in its implementation. The review of the literature has shown that conceptions about supervision have been changing considerably over time, both in health and in education. The UFC has accumulated significant experience in medical education and has participated in this Project since its implementation in 2013. Therefore, we performed a qualitative research, known as action research, with the seventeen supervisors of this institution linked to this Project. The research was organized in four phases: exploratory and planning; semi-structured interviews; workshops; and evaluation. We adopt as theoretical basis for this study the pragmatic analysis presented by Habermas (2004), structured from the linguistic theory of Humboldt. All research was based on the principles of bricolage. The analysis showed that supervisors play diverse roles in daily practices, which require skills beyond those acquired in the usual training processes. The research fostered the cognitive content of moral discussions making it possible to validate consensus, promote intersubjective agreements and negotiate commitments. The action plan portrayed the reflections on the potential of supervision to qualify the performance of primary care professionals and to strengthen continuing education. In addition, it pointed out needs for improvement of the Project by the National Coordination.